Bioprospection of Potential Medicinal Plant Diversity in the Wana Lestari Community Forest, Karang Sidemen Village - Niechi Valentino; Sitti Latifah; Muhammad Anwar Hadi; Budhy Setiawan; Irwan Mahakam Lesmono Aji (Postgraduate, University of Mataram, 2022)
Medicinal potential plants that are scattered in community forest areas have opportunities that can be utilized in ecosystem-based sustainable forest management. Considering the potential medicinal plants have played a major role in maintaining the health condition of the community around the forest from generation to generation. This study aims to determine the abundance of medicinal plant species in the Wana Lestari Community Forest, Karang Sidemen Village based on the value of the Ecological Index. The research method used is Stratified Random Sampling with Replacement with a total of 59 research sample plots. The results showed that the types of medicinal plants at the level of trees, poles, saplings, seedlings, shrubs, bush, terna, lianas, and ferns which had the highest Importance Value Index (IVI) were D. zibethinus (72.42%) trees level, D. zibethinus (111.82%) poles level, C. canephora (144.98%) saplings level, C. canephora (109.64%) seedlings level, C. frutescens L (70.33%) shrubs level, H. capitata Jacq. (103.07%) bushs level, C. prostrata (26.69%) ternas level, M. cordata (92.46%) lianas level, and D. esculentum (169.39%) ferns level. The Morishita index shows that most species at the trees, shrubs, bushes, ternas, lianas, and ferns levels spread in groups while most of the plant species at the pole, sapling, and seedling levels spread randomly. In addition, the Species Diversity Index (H') of medicinal plants showed values ​​at the level of trees (2.08), poles (1.92), saplings (1.16), seedlings (1.72), shrubs (1.8), bushs (1.79), ternas (2.94), lianas (1.44) and ferns (0.53). Furthermore, the value of the species richness index (R1) of plants with medicinal potential is at the level of the tree (2.68), poles (2.82), saplings (1.93), seedlings (1.72), shrubs (1.84), bushs (2.22), ternas (4.17), lianas (1.87) and ferns (0.38). The evenness index value (E') of medicinal potential plants is at the level of trees (0.73), poles (0.75), saplings (0.48), seedlings (0.61), shrubs (0.92), bushs (0.7), ternas (0.82), lianas (0.58) and ferns (0.49).